In vivo electrophysiological characterization of TASK-1 deficient mice - Petric, Stella; Aller, Maria I. (Cellular physiology and biochemistry, 2012)
Background/Aims: TASK-1 is a potassium channel predominantly expressed in heart and brain. We have previously shown that anesthetized TASK-1-/-mice have prolonged QT intervals in surface electrocardiograms (ECGs). In addition, heart rate variability quantified by time and frequency domain parameters was significantly altered in TASK-1-/-mice with a sympathetic preponderance. Aims of the present study were the analysis of QT intervals by telemetric ECGs, to determine potential influences of anesthesia and β-adrenergic stimulation on repolarization in surface ECGs, to investigate in vivo electrophysiological parameters by intracardiac electrical stimulation and to quantify heart rate turbulence after ischemia/reperfusion or ventricular pacing in TASK-1+/+ and TASK-1-/-mice. Methods: Rate corrected QT intervals (QTc) were recorded in conscious mice by telemetry and in surface ECGs following administration of various anesthetics (tribromoethanol (Avertin®), pentobarbital and isoflurane). TASK-1+/+ and TASK-1-/mice were characterized by programmed electrical stimulation using an intracardiac octapolar catheter. The baroreceptor reflex was analyzed by heart rate turbulence (turbulence onset and slope) after ischemia/reperfusion and by stimulated premature ventricular contractions. Results: Telemetric and surface ECGs in mice sedated with Avertin®and pentobarbital, showed a significantly lengthened rate corrected QT interval in TASK-1-/-mice (telemetry: TASK-1+/+ 43±3ms vs. TASK-1-/-49±5ms, n=6, p<0.05; Avertin®: TASK-1+/+ 36±8ms vs. TASK-1-/-48±4ms, n=13/16, p<0.0001). The prolongation of the QT interval was most pronounced at lower heart rates. Isoflurane, known for its stimulatory effects on the TASK channel family, attenuated the rate corrected QT interval prolongation in TASK-1-/-mice. Intracardiac electrical stimulation revealed normal values for electrical conduction and refractoriness. No significant arrhythmias after atrial and ventricular burst stimulation were induced before and after adrenergic challenge in both genotypes. Turbulence onset after premature ventricular contraction was significantly altered in TASK-1-/-mice. Conclusion: TASK-1-/-mice exhibit a phenotype of QT prolongation, which distinct relation to heart rate. TASK-1 deficiency does neither alter key electrophysiological parameters nor increases atrial/ventricular vulnerability after electrical stimulation. The heart rate response after premature ventricular contractions is significantly abolished indicating a diminished baroreceptor reflex in TASK-1-/-mice.